2012
DOI: 10.1155/2012/292414
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Dissection and Rupture of a Popliteal Cyst: A Case Report

Abstract: Popliteal cysts are swellings in the popliteal fossa due to enlargement of the gastrocnemius semimembranous bursa. These cysts might burst, and they usually rupture posteriorly and inferiorly with severe pain in the calf. We describe a patient with popliteal cyst that dissected proximally and ruptured in the soft tissue of the thigh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Proximal cyst rupture into the soft tissue of the thigh has also been reported. 26 DUS & MRI avoids misdiagnosis and inappropriate treatment, 5 [Triveda S et al 2015], with some authors considering DUS the imaging of choice. 27 Kim et al 2014, concluded that DUS differentiated purely cystic masses from more solid lesions and could exclude a DVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximal cyst rupture into the soft tissue of the thigh has also been reported. 26 DUS & MRI avoids misdiagnosis and inappropriate treatment, 5 [Triveda S et al 2015], with some authors considering DUS the imaging of choice. 27 Kim et al 2014, concluded that DUS differentiated purely cystic masses from more solid lesions and could exclude a DVT.…”
Section: Discussionmentioning
confidence: 99%
“…In identifying fluid behind the calf muscle connected to a popliteal cyst, or calf muscle dissection, DUS useful in confirming BC rupture, and excluding other causations of posterior lower limb pain such as cellulitis, or medial head of gastrocnemius or Achilles tendon tear. 26 US-guided aspiration with corticosteroid injection is a wellknown and reputedly safe conservative management for symptomatic BC. The steroid appears to be more effective when injected into the Baker's cyst directly compared to injecting into the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, ruptured intramuscular Baker's cyst may cause compressive neuropathy of the posterior tibial nerve. While complications associated with Baker's cysts include dissection, rupture, pseudothrombophlebitis, leg ischemia, nerve entrapment, and compartment syndrome 8) , hematoma is an uncommon complication.…”
Section: Discussionmentioning
confidence: 99%
“…В большинстве случаев разрыв возникает остро, но возможен и субклинический вариант, когда наблюдается регулярное «подтекание» небольших порций жидкости [16].…”
Section: разрыв кбunclassified